Antibody Levels in Ethiopian Children Five Years after Vaccination with Two Different Doses of Hepatitis B Vaccine: Is There a Need for Booster Vaccine? - Edemariam Tsega; John Horton; Erik Nordenfelt; B-J Hansson; Belachew Tafesse; Gizachew Wolde-Hawariat; Johan Lindberg (Canadian Journal of Gastroenterology)
It was hypothesized that, following effective initial vaccination, a booster dose of hepatitis B vaccine will not be necessary in areas of hyperendemicity for hepatitis B virus (HBV) infection. A total of 314 Ethiopian children, ranging from two to 14 years old, were alternatively vaccinated with 10 and 20 µg hepatitis B vaccine doses, using the initial, one- and six-month schedule. Five years later, 210 of the vaccinees were retested for anti-HBV surface antibody titres. Both 10 and 20 µg doses of hepatitis B rDNA yeast vaccine were equally immunogenic and protective against HBV infection for at least five years despite marked reduction of mean antibody levels and geometric mean titres, with 11% of the vaccinees showing antibodies below the protective level. For firm further recommendations a longer follow-up period of vaccinees is suggested.